Alice Basso, Non ditelo allo scrittore (Milano, Garzanti, 2017, 318 pp. ISBN 9788811673446) (Altre Modernità, 2018)
Alice Basso, Non ditelo allo scrittore (Milano, Garzanti, 2017, 318 pp. ISBN 9788811673446)di Ilaria Villa